(untitled) (Bangladesh Journal of Infectious Diseases, 2017)
Background: There are many risk factors which can influence the causation of kala azar in Bangladeshi people. Objective: The aim of the present study is to describe the living pattern and behavioral risk factors of kala-azar among a case series of Bangladeshi patients. Method: This case control study was carried out at inpatient department of Community Based Medical College Hospital, Mymensingh from July 2010 to June 2011, for a period of 1(one) year. The study samples were clinically and parasitologically confirmed kala-azar cases. The controls were rK 39 strip test negative hospitalized cases admitted for other reason. Results: Univariate analysis showed that age, sex, marital status, average number of person living in room frequently, goat sharing in sleeping room, number of kala-azar treatment in living family members, nearest distance of known kala-azar, were risk factors. Multivariate analysis showed that Marital status (OR=6.940, 95%CI=2.710-17.772, P=.001), Number of family member living in the room were significant risk factors (OR=1.786, 95%CI=1.097-2.907, P=0.020) for kala-azar. Conclusion: These findings have important practical implications because they suggest that these measures, along with appropriate vector control and improved treatment facilities in rural areas, may be particularly effective in reducing the incidence of kala-azar and its transmission of infection by sand fly vectors. Bangladesh Journal of Infectious Diseases 2016;3(2):29-35